Extended-spectrum β-lactamase producing E. coli in urinary tract infections: A two-center, cross-sectional study of prevalence, genotypes and risk factors in Amman, Jordan - Sayida A. Al-Jamei; Abla Y. Albsoul; Faris G. Bakri; Amal G. Al-Bakri (Elsevier, 2019)
Background: To determine the prevalence, phenotypes, and genotypes of extended spectrum β-lactamase (ESBL)-producing Escherichia coli (E. coli) among patients with urinary tract infection along with identifying the associated risk factors. Methods: A cross-sectional study was conducted at two tertiary hospitals in Amman, Jordan between June and October, 2016. One hundred twenty one E. coli isolates from hospitalized patients with urinary tract infection were phenotypically assessed for ESBL production using the double disc diffusion test. Positive isolates to ESBL production were further genotyped using multiplex PCR. A nested case-control study was used to determine the independent risk factors. Results: ESBL-producing E. coli were found in 75/121 (62%) isolates. Molecular genotyping demonstrated that CTX-M group1 (42.7%) predominated followed by combination of SHV and CTX-M group1 (20%). In the regression model, previous hospitalization and use of urinary catheter were identified as independent risk factors for ESBL-producing E. coli infections. Conclusion: We report a high prevalence of ESBL-producing E. coli which is in concordance with other studies from developing countries. Additionally, CTX-M group1 has emerged as the predominant ESBL produced by E. coli, which is consistent with reported results throughout the world. Independent risk factors to UTI infections due to ESBL-producing E. coli include previous hospitalization and use of urinary catheter. Keywords: E. coli, ESBL, CTX-M group 1, Urinary tract infection, Risk factors